Use of color traps and alcoholic attractants for the capture of the coffee berry borer (Hypothenemus hampei) in highly infested coffee plantations. (2019)
Mass capture is a technique widely considered in the control of the coffee plague of greater economic importance in the world. This work was carried out in the province of Rodríguez de Mendoza, Amazonas region, Peru, with the objective of analyzing the effect of artisanal traps of different colors and attractive alcoholics in the capture of adults of coffee borer adults, Hypothenemus hampei, in a highly infested plantation, and its implication in reducing the incidence of damage caused by this pest. Six treatments generated from the combination of levels of the following color factors (transparent, red and green) and alcoholic attractants (without and with coffee essence) were evaluated. The test was conducted in a randomized complete block experiment design. The incidence of coffee berry bore damage was measured in periodic measurements every 30 days, while the capture levels (adults / trap) were evaluated every 15 days. The obtained data was subjected to an analysis of covariance, detecting statistically significant differences between the treatments and once applied the multiple comparisons test, specifically minimum significant difference, it was evidenced that the red trap without essence of coffee captured a greater number of adults (with a maximum of 4,000 adults / trap / week) and proved to be more effective in reducing the incidence (43.7 % less than the initial incidence). On the other hand, the least effective trap was the transparent one without coffee essence.